Aspects of using computer programs in teaching higher mathematics at university - Ekaterina V. Mazurenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to teaching first-year students in the study of discipline "Higher mathematics" with the use of computer programs. The features of the use of various computer programs for different levels of preliminary preparation of the students are discussed. It is shown that computer packages are not quite intensively used in the teaching process, despite their significant educational potential. The possibility of applying specialized mathematical packages, and the use of the most common office programs are analyzed. The possibility of using mathematical software in the study of linear algebra by first-year students of a technical university is justified.